ANALISIS PENGARUH HARGA, FASILITAS, PROMOSI TERHADAP KEPUASAN KONSUMEN PAND’S MUSLIM DEPARTEMENT SEMARANG - Adiatma, Maulana Teguh; Widjajanti, Kesi (Solusi, 2023)
This study aims to determine the effect of price, facilities and promotions at Pand's Muslim Department Store Semarang.The population of this study are consumers who buy products at Pand's Muslim Department Store Semarang. The sample used in this study was 96 respondents, the sample was taken using purposive sampling method. This study used quantitative research methods with data collection methods through questionnaires and data analysis using SPSS 25 which included validity tests, reliability tests, classic assumption tests which included data normality tests, multicollinearity tests, and heteroscedasticity tests, multiple regression analysis, hypothesis testing using test t and test R2 .The results of this study indicate that all independent variables, namely price, facilities and promotions have a positive and significant effect on consumer satisfaction (Y). Based on the value that the value of the adjusted R square in the regression model was obtained at 0.156, which means that 15.6 percent of the consumer satisfaction variable can be explained by the price, facilities and promotion variables while the remaining 84.4 percent is explained by other variables outside this study.